Prolonged survival of a patient with active MDR-TB HIV co-morbidity: insights from a Mycobacterium tuberculosis strain with a unique genomic deletion - Rubinstein, Mor; Makhon, Andrei; Losev, Yelena; Valenci, Gal Zizelski; Gatt, Yair E.; Margalit, Hanah; Fass, Ephraim; Kutikov, Ina; Murik, Omer; Zeevi, David A.; Savyon, Michal; Tau, Luba; et al. (Frontiers in Medicine, 2023)
Coinfection of HIV and multidrug-resistant tuberculosis (MDR-TB) presents significant challenges in terms of the treatment and prognosis of tuberculosis, leading to complexities in managing the disease and impacting the overall outcome for TB patients. This study presents a remarkable case of a patient with MDR-TB and HIV coinfection who survived for over 8 years, despite poor treatment adherence and comorbidities. Whole genome sequencing (WGS) of the infecting Mycobacterium tuberculosis (Mtb) strain revealed a unique genomic deletion, spanning 18 genes, including key genes involved in hypoxia response, intracellular survival, immunodominant antigens, and dormancy. This deletion, that we have called “Del-X,” potentially exerts a profound influence on the bacterial physiology and its virulence. Only few similar deletions were detected in other non-related Mtb genomes worldwide. In vivo evolution analysis identified drug resistance and metabolic adaptation mutations and their temporal dynamics during the patient’s treatment course.